Is the operative delivery rate in low-risk women dependent on the level of birth care? : a randomised controlled trial - Bernitz, Stine; Rolland, Rune; Blix, Ellen; Jacobsen, Morten; Sjøborg, Katrine Dønvold; Øian, Pål (BJOG: An International Journal of Obstetrics & Gynaecology, 2011)
Objective: To investigate possible differences in operative delivery rate among low-risk women, randomised to an alongside midwifery-led unit or to standard obstetric units within the same hospital. Design: Randomised controlled trial. Setting: Department of Obstetrics and Gynaecology, Østfold Hospital Trust, Tromsø, Norway. Population: A total of 1111 women assessed to be at low risk at onset of spontaneous labour. Methods: Randomisation into one of three birth units: the special unit; the normal unit; or the midwife-led unit. Main outcome measures: Total operative delivery rate, augmentation, pain relief, postpartum haemorrhage, sphincter injuries and intrapartum transfer, Apgar score <7 at 5 minutes, metabolic acidosis and transfer to neonatal intensive care unit. Results: There were no significant differences in total operative deliveries between the three units: 16.3% in the midwife-led unit; 18.0% in the normal unit; and 18.8% in the special unit. There were no significant differences in postpartum haemorrhage, sphincter injuries or in neonatal outcomes. There were statistically significant differences in augmentation (midwife-led unit versus normal unit RR 0.73, 95% CI 0.59–0.89; midwife-led unit versus special unit RR 0.69, 95% CI 0.56–0.86), in epidural analgesia (midwife-led unit versus normal unit RR 0.68, 95% CI 0.52–0.90; midwife-led unit versus special unit RR 0.64, 95% CI 0.47–0.86) and in acupuncture (midwife-led unit versus normal unit RR 1.45, 95% CI 1.25–1.69; midwife-led unit versus special unit RR 1.45, 95% CI 1.22–1.73). Conclusions: The level of birth care does not significantly affect the rate of operative deliveries in low-risk women without any expressed preference for level of birth care.